The level of the emergency health workers professionals' knowledge about chemical, biological, radiological, and nuclear (CBRN) hazards: The case of Turkey - Bulut, Aliye; Atici, Erhan (Sage Publications Inc, 2024)
BACKGROUND: It is crucial that emergency health workers respond to people exposed to chemical, biological, radiological and nuclear agents appropriately and in a timely manner. OBJECTIVE: This study aims to find out how much Turkish emergency health workers know about chemical, biological, radiological, and nuclear hazards, as well as identify what possible factors contribute to their level of knowledge. METHOD: The data were collected from 321 participants using a personal information form as well as a questionnaire about chemical, biological, radiological and nuclear hazards prepared in accordance with the literature. RESULTS: The results revealed that the place of residence and status of choosing the profession willingly showed no difference in terms of being trained on chemical, biological, radiological and nuclear hazards (p > 0.05). Likewise, the participants under the age of 25 years, who were single and had a tenure of less than 10 years highly believed that they did 'not have a sufficient grasp of chemical, biological, radiological and nuclear hazards'. Women also highly believed that they did 'not have a solid grasp of chemical, biological, radiological and nuclear hazards.' CONCLUSIONS: Healthcare professionals who work in high-risk zones should be given compulsory training about chemical, biological, radiological and nuclear hazards so that they become more aware of how to best deal with such situations.
Keywords: CBRN threats; emergency health workers; health personnel; knowledge level